2022
DOI: 10.1021/acs.jpcc.2c04807
|View full text |Cite
|
Sign up to set email alerts
|

Band Structure Engineering of 2D Heterotriangulene Polymers by Incorporating Acetylenic Linkages for Photocatalytic Hydrogen Production

Abstract: By performing first-principles calculations, we propose to introduce acetylenyl (−CC−) into the honeycomb kagome lattices of heterotriangulenes (HT)-based two-dimensional (2D) polymers to construct 2D HT-polyynes with tunable electronic and optical properties for photocatalysis. It is found that the band gap can be effectively reduced to a moderate value of around 2.00 eV by increasing the number of −CC– (n = 1, 2, 3) in the skeletons, contributing to enhanced light-harvesting ability in the visible range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Similar to DMI, EMA, which is determined by λ and K eff , is also of great importance for establishing the topological magnetism. ,, As unveiled above, K eff is sensitively dependent on the electronic state around the Fermi level. In heterostructures, the electronic state can be easily manipulated via applying an external electric field, which holds the possibility to tune K eff as well as the topological magnetism.…”
mentioning
confidence: 96%
“…Similar to DMI, EMA, which is determined by λ and K eff , is also of great importance for establishing the topological magnetism. ,, As unveiled above, K eff is sensitively dependent on the electronic state around the Fermi level. In heterostructures, the electronic state can be easily manipulated via applying an external electric field, which holds the possibility to tune K eff as well as the topological magnetism.…”
mentioning
confidence: 96%
“…9 A promising way to tune the electronic and magnetic properties of triangulenes is through doping and edge passivation. 12,13 Kan et al 14 have studied isolated 3-triangulene and demonstrated that it is possible to manipulate the occupation of π orbitals by replacing the central carbon atom with nitrogen or boron. They have also explored triangulene crystals and showed through the use of density functional theory (DFT) calculations that N-doping tunes the magnetic order from antiferromagnetic to ferromagnetic.…”
Section: Introductionmentioning
confidence: 99%
“…Against a background of excessive use of fossil energy and serious environmental pollution, it is crucial to develop green, efficient, and renewable energy sources. Hydrogen energy is one of the best alternative energy sources because it is renewable and pollution-free. Photocatalytic hydrogen production technology is considered to be a sustainable strategy to solve growing environmental problems and the energy shortage due to its ability to convert solar energy to hydrogen energy. Semiconductor photocatalysts have been extensively studied for H 2 evolution since the groundbreaking work on the photocatalytic splitting of TiO 2 for hydrogen production was reported in 1972, including carbides, oxides, sulfides, and phosphates. TiO 2 has been widely studied due to its excellent photocatalytic activity and nontoxicity. However, the band gap of TiO 2 is about 3.2 eV, meaning that it can absorb only ultraviolet light, which means that most of the sunlight cannot be used .…”
Section: Introductionmentioning
confidence: 99%